2022
DOI: 10.1186/s40249-022-01029-0
|View full text |Cite
|
Sign up to set email alerts
|

Decreased influenza vaccination coverage among Chinese healthcare workers during the COVID-19 pandemic

Abstract: Background Healthcare workers (HCWs) were the priority group for influenza vaccination, in China during the 2020/2021 and 2021/2022 influenza seasons. However, vaccination rates in HCWs have always been low. This study investigated influenza vaccination status among Chinese HCWs and analyzed the factors driving vaccination. Methods We provided electronic questionnaires to HCWs from January 27, 2022 to February 21, 2022, using the WeChat platform "B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…Vaccines can protect their occupational health and safety and highlight the duties, rights, and responsibilities for health and safety at work. As reported by a previous study, IVC of HCWs (67%) had substantial growth after the official document released in China, which required all medical institutions to provide IV [ 16 ], but dropped dramatically due to the COVID-19 pandemic [ 6 ]. Fortunately, we did not observe a decline in IV willingness for the coming season (74.89%) which may attest to the advantage of free IV for HCWs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Vaccines can protect their occupational health and safety and highlight the duties, rights, and responsibilities for health and safety at work. As reported by a previous study, IVC of HCWs (67%) had substantial growth after the official document released in China, which required all medical institutions to provide IV [ 16 ], but dropped dramatically due to the COVID-19 pandemic [ 6 ]. Fortunately, we did not observe a decline in IV willingness for the coming season (74.89%) which may attest to the advantage of free IV for HCWs.…”
Section: Discussionmentioning
confidence: 99%
“…The acceptance of the influenza vaccine was counted by each BeSD item. For the 3Cs’ variables, statements of confidence, convenience, and complacency, adopted from previous studies were included [ 6 ], but the average scores of each factor in the 3Cs’ model were calculated by a 5-point Likert scale ranging from 1 = “not at all” to 5 = “fully compatible/right/follow” to identify factors influencing vaccine hesitancy.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…From February through August 2022, influenza activity was at its highest level compared to similar periods since the start of the coronavirus disease 2019 (COVID-19) pandemic globally (2). As the priority group recommended for influenza vaccination during the COVID-19 pandemic, healthcare workers (HCWs), including public health workers (PHWs), have a greater chance of contracting influenza viruses; this poses a greater risk of transmission (3). PHWs refer to those who are engaged in public health services and vaccination work in the Center for Disease Control and Prevention (CDC) system, community health service centers, or township health centers.…”
Section: What Is Added By This Report?mentioning
confidence: 99%
“…PHWs refer to those who are engaged in public health services and vaccination work in the Center for Disease Control and Prevention (CDC) system, community health service centers, or township health centers. Previous surveys have shown that willingness and influence factors of front-line staff involved in the work of influenza control are of higher concern ( 4 - 5 ). The research mainly focused on assessing PHWs’ attitudes toward influenza vaccination in 2022–2023.…”
mentioning
confidence: 99%